Designing of the indacenodithiophene core-based small molecules for optoelectronic applications: A DFT approach. (1st May 2022) - Akram, Sahar Javaid; Iqbal, Javed; Ans, Muhammad; El-Badry, Yaser A.; Mehmood, Rana Farhat; Khera, Rasheed Ahmad
Highlights: Five new O -IDTBR based acceptor materials are designed using structural variation with different end-capped acceptor units. The investigated molecules exhibit better optical and electronic properties such as reduced band gaps and enhanced absorption. Strong acceptor groups increase the fill factor and dipole moment of the designed molecules. Abstract: With the intention of utilizing computational methods to amplify the photovoltaic ability of organic solar cells, DFT (density functional theory) and TD-DFT (time-dependent density functional theory) methods were employed on five newly-designed indacenodithiophene based A-D-A (acceptor–donor-acceptor) type small molecules. These (IDT1-IDT5) non-fullerene acceptor-based molecules have a central core of the O-IDTBR molecule with the substitution of different substantial acceptors on the peripheral edges. The optical parameters, electrical properties, and charge transfer abilities of these molecules were carefully analyzed through MPW1PW91/6-31G (d, p) method. Some optical, as well as chemical, parameters of IDT1, IDT4, and IDT5 were found to be superior to the reference molecules. It was also revealed from the frontier molecular orbitals (FMOs) and density of states (DOS) graphs that newly attached acceptor groups significantly enhanced the distribution of charge density in the molecules under study, especially in IDT1. The ability to consistently transfer charges was disclosed through the TDM graphs. The charge transfer mobilities of some of the molecules being comparable to the reference molecule, with that of IDT2 being the lowest, envisioned better maneuverability of the charge carriers. The open-circuit voltage of the IDT1 with PC61 BM acceptor and all others with PTB7-Th donor was calculated, given that IDT1 having higher HOMO and LUMO orbitals will act as an acceptor, vice versa. Lastly, the high values of fill factor predicted remarkable power conversion efficiency of all the investigated molecules. Consequently, all the computed parameters commend the ability of our modified molecules in the field of photovoltaics.